Implementation of Digital Marketing Strategy in Equivalency Education Program - Wulandari, Mega; Riyanto, Yatim; Widodo, Widodo (Universitas Negeri Semarang, 2024)
The rapid development of digital technology has significantly influenced marketing strategies in various fields, including education. Equivalency education programs, which provide opportunities for individuals to attain education equivalent to formal schooling, must adopt effective digital marketing strategies to reach wider audiences and increase enrollment. This research aims to explore how digital marketing strategies are implemented in equivalency education programs and evaluate their effectiveness in promoting these programs. This research employs a descriptive qualitative method, gathering data through observation, documentation, and in-depth interviews with key informants managing equivalency education programs. The digital marketing strategy involves several stages, including situation analysis, digital marketing planning, goal setting, strategy creation, execution, budget preparation, and marketing evaluation. The implementation primarily uses print media, websites, and social media platforms such as Instagram, Facebook, and WhatsApp Business. The analysis shows that digital marketing, particularly through social media platforms, has proven to be highly effective in promoting equivalency education programs. Digital marketing strategies play a crucial role in increasing the visibility and appeal of equivalency education programs. Social media, particularly Instagram and WhatsApp Business, are identified as the most impactful tools for reaching the target audience. This study highlights the specific stages and tools that make digital marketing particularly effective in the context of equivalency education programs, offering insights into best practices for other educational institutions looking to enhance their promotional efforts.